Factors influencing treatment burden in colorectal cancer patients undergoing curative surgery: A cross‐sectional study. (9th March 2021) - Husebø, Anne M. L.; Dalen, Ingvild; Richardson, Alison; Bru, Edvin; Søreide, Jon A.
Abstract: Objective: To describe the severity of treatment burden in surgically treated colorectal cancer (CRC) patients and examine associations between treatment burden and demographic and clinical variables. Methods: This cross‐sectional study recruited 134 patients diagnosed with Dukes' stage A‐C CRC between 2016 and 2018 who underwent curative surgery. The Patient Experience with Treatment and Self‐management (PETS) questionnaire assessed treatment burden domains of 'workload', 'stressors' and 'impact' between 6 weeks and 18 months after primary surgery. Results: Highest scores were observed for difficulty with healthcare services (median score 33.3), physical and mental fatigue (median score 30.0) and medical information (median score 26.8). Younger age, low education level or no cohabitants were significantly associated with higher workload PETS scores ( p < 0.05, 0.013, p = 0.047, respectively). Higher PETS stressors scores were significantly associated with younger age ( p = 0.006), lower education level ( p = 0.016), and high comorbidity ( p = 0.013). Higher PETS impact scores were significantly associated with the female sex ( p = 0.050), younger age ( p = <0.001–0.003), lower education ( p = 0.003), no cohabitants ( p = 0.003), high comorbidity ( p = 0.003) and cancer stage Dukes A ( p = 0.004). Conclusions: A seamless and supportive healthcare system beyond hospitalisation targeting CRC subpopulations in danger of high treatment burden may improve patients' self‐management experience.